Emerging trends and applications in information communication technologies - Chowdhry, Bhawani Shankar; Shaikh, Faisal Karim; Hussain, Dil Muhammad Akbar; Uqaili, Muhammad Aslam ([S.l.] : Springer, 2012)
This book constitutes the refereed proceedings of the Second International Multi-topic Conference, IMTIC 2012, held in Jamshoro, Pakistan, in March 2012. The 51 revised full papers presented were carefully reviewed and selected from 205 submissions. The papers address topics from information communication technologies.
Keywords: a